Eliminating online child sexual abuse material - Brown, Rick (Crime science series, 2023)
This book uses a crime science approach to explore the ways in which child sexual abuse material (CSAM) can be tackled. It describes the CSAM ecosystem, focusing on the ways in which it is produced, distributed and consumed and explores different interventions that can be used to tackle each issue. Eliminating Online Child Sexual Abuse Material provides a methodical approach to unpacking and understanding this growing problem, identifies approaches that have been shown to work and offers alternatives that might be tried. This analysis is set within a crime sciences context that draws on rational choice, routine activities, situation crime prevention and environmental criminology to better understand the nature of the problem and the potential ways in which it may be solved. This book is intended for policy-makers and practitioners working in child protection, online harms and related areas and for students studying sexual violence or internet-related crime. The book will also be of interest to crime scientists as it provides another example of how the approach can be used to understand and reduce crime